Multifuncionalidade da agricultura familiar no município de Campina das Missões, RS, Brasil. - Reis, Janete Teresinha (2015)
The present research aimed at analyzing the roles of multifunctional family-based agriculture in the landscape, considering the city of Campina das Missões as the locus of this research. It was proposed the study of several aspects in the economic exploitation of land used for family agriculture, being adopted the line of epistemology as the methodology for the qualitative research at the city level. Being so, this research was grounded in a critical, dialectical, theoretical and methodological approach, as it was the most suitable for conducting the study proposed. The main reason that took the citizens of Campina das Missões to modify the landscape of this locus over the years is the need to increase their family income and to improve living condition. Changes in the natural dynamics of elements in the landscape interfering in the natural resources can be added up to that as well. So, different stages in this process were marked by alterations affecting the environment, both positively and negatively. However, the third stage, guided by the modernization of agriculture, set significant changes in the environment. Therefore, the cultural knowledge adopted is a way to improve the family income, without leaving aside the agricultural and livestock production, at least in a subsistence level. Nevertheless, many family farmers are investing in other areas, and being adopted the multifunctionality, they turn themselves to the cultural knowledge to add value to the production and promote the reorganizations and transformation of local landscape.